Reasons for Staying Alive in Suicide Attempters Across Different Ethnic Groups Admitted to UMMC - Koh, O.H.; Zuraida, N.Z.; Low, C.C.; Jesjeet, S.G.; Bharathi, V.; Parameswaran, R.; Sharmilla, K. (2002)
Previous studies showed different rate of suicide attempt in different ethnicgroups In Malaysia. However, most studies were aimed at assessing the riskfactors for the attempt rather than for the reasons suicide attempters chose to liveafter the attempt. Aim: The aim of this study was to describe the associationbetween different ethnic groups, suicide ideation, hopelessness and the reasonsfor staying alive in suicide attempters admitted to University Malaya Medical Center, Kuala Lumpur. Methods: 40 suicide attempters were assessed on suicidehistories, psychiatric diagnoses, Scale for Suicide Ideation (SSI), Hopelessness Scale (HS), and Reason for Living Inventory (RLI). Results: 16(40%) comprised ofMalays, 14(35%) were Chinese, 8(20%) were Indians and 2(5%) were others. TheRLI scores showed statistically significant inverse correlation with SSI and HS(r=-0.5, p<0.05 each). There was significant association between ethnic groupsand SSI score (F=3.3, p=0.03). The Indians had significantly higher mean score inSSI compared to the Malays (p=0.02). There was also significant association between ethnic groups and RLI score (F=3.0, p=0.04). The Indians had significantly lower mean score of total RLI compared to the Malays (p=0.03). The Indians alsohad lower mean score for fear of social disapproval compared to the Chinese(p=0.02) and the Malays (p=0.01). Conclusion: Among suicide attempters whowere admitted to UMMC, the Indian population scored highest in having suicideideation and had lowest scores on their reasons for staying alive after the attempt.This was obvious in terms of less fear of social disapproval in their suicide attemptbehaviour.